ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KECURANGAN LAPORAN KEUANGAN DENGAN TEORI FRAUD DIAMOND - Thirza Wailan Putri Seruni (2020)
This research is a quantitative study that aims to analyze the effect of factors in fraud diamond theory and the possibility of financial statement fraud. Diamond fraud theory is measured by pressure (external pressure), opportunity (nature of industry), rationalization (TATA), capability (director changes). The method used is purposive sampling. The sample consisted of 135 companies from 160 manufacturing companies listed on the Indonesia Stock Exchange in 2016 - 2018. Data were analyzed using descriptive statistical analysis and logistic regression with some help of programming data using SPSS (Statistical Product and Service Solution) 25th. The results showed that the external pressure, nature of industry, and rationalization affected the financial statement fraud, while the director changes variable have no effect on the financial statement fraud.